2022
DOI: 10.3389/fpubh.2022.917781
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban differences in prevalence of and risk factors for refractive errors among school children and adolescents aged 6–18 years in Dalian, China

Abstract: PurposeTo assess the prevalence of refractive errors (REs) in school children aged 6–18 years in urban and rural settings in Dalian, Northeast of China.MethodsThis is a school-based cross-sectional survey using multi-stage randomization technique. Six- to eighteen-year-old school children from elementary schools, junior and senior high schools from a rural area and an urban area in Dalian were included in December 2018. All subjects underwent a comprehensive questionnaire and eye examination.ResultsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…Considering the 47.8% overall prevalence of refractive error (17.1% in boys and 30.6% in girls), our screened population had a considerably higher prevalence. This difference verifies the findings of previous studies, which reported different prevalence rates within countries and even among people of the same ethnic background [4][5][6]. Furthermore, it indicates the importance of vision screening programs among various communities or areas in the same country to discover the actual magnitude of this avoidable and prevalent cause of visual impairment [3].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Considering the 47.8% overall prevalence of refractive error (17.1% in boys and 30.6% in girls), our screened population had a considerably higher prevalence. This difference verifies the findings of previous studies, which reported different prevalence rates within countries and even among people of the same ethnic background [4][5][6]. Furthermore, it indicates the importance of vision screening programs among various communities or areas in the same country to discover the actual magnitude of this avoidable and prevalent cause of visual impairment [3].…”
Section: Discussionsupporting
confidence: 86%
“…Using the same definition, myopia accounted for 63.2% of students with refractive errors in the present study, which is significantly less than that in the screened population. This indicates the difference in the prevalence rate of the type of refractive error within countries and even among people of the same ethnic background [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 For example, Wang et al reported myopia prevalence of 82.71% and 72.76% among students aged 6–18 years in urban Dalian city and rural areas of China, respectively. 16 Similarly, Peng et al found that the prevalence of myopia in urban and rural regions in Anhui was 68.1% and 63.7%, 17 respectively.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous studies have demonstrated varying rates of myopia among populations with comparable genetic backgrounds but varying degrees of urbanisation 15. For example, Wang et al reported myopia prevalence of 82.71% and 72.76% among students aged 6–18 years in urban Dalian city and rural areas of China, respectively 16. Similarly, Peng et al found that the prevalence of myopia in urban and rural regions in Anhui was 68.1% and 63.7%,17 respectively.…”
Section: Introductionmentioning
confidence: 99%